The geomagnetic pulses level variations accompanied the rocket launches on background solar terminator - Смирнова, Е. О.; Черногор, Л. Ф. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
Results from the system spectral analysis of temporal variations in the geomagnetic field horizontal components, which are associated with the orbital maneuvering subsystem engine burns and the firing of the booster stages of the Soyuz and Proton rockets launched at the Plesetsk and the Baikonur cosmodromes and with the solar terminator in the background, are presented for the second half of 2017. The main signal parameters related to the disturbances in the geomagnetic field have been obtained. In order to select the geomagnetic disturbances of magnetospheric origin, an intercomparison between the observed wave disturbances and the B z component of the interplanetary magnetic field has been made.